2019
DOI: 10.1108/ijopm-08-2017-0484
|View full text |Cite
|
Sign up to set email alerts
|

Managing servitization in product companies: the moderating role of service suppliers

Abstract: Purpose-The purpose of this paper is to study service innovation in product companies (servitization) by considering the relationship (moderation) between product companies and service suppliers. Methodology-Using a relational view of the firm, we propose that there are three main business dimensions that product companies have to manage in servitization and that the support of service suppliers can moderate the effects of these dimensions on the benefits obtained from the Product-Service System (PSS) delivere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(118 citation statements)
references
References 110 publications
(225 reference statements)
6
110
1
1
Order By: Relevance
“…High levels of MSO are also required for the impact of servitization on a number of other financial and nonfinancial performance constructs and indicators to be positive. These are customer satisfaction and loyalty, return on investment, return on assets and sales growth (Zhao et al, 2017;Li et al, 2018;Ayala et al, 2019;Frank et al, 2019;Yan et al, 2019). Furthermore, when organizations have a dedicated service executive (OS) or outsource the service provision to specialized providers, performance improves in terms of differentiation and customer satisfaction (Bustinza et al, 2015).…”
Section: -mentioning
confidence: 99%
“…High levels of MSO are also required for the impact of servitization on a number of other financial and nonfinancial performance constructs and indicators to be positive. These are customer satisfaction and loyalty, return on investment, return on assets and sales growth (Zhao et al, 2017;Li et al, 2018;Ayala et al, 2019;Frank et al, 2019;Yan et al, 2019). Furthermore, when organizations have a dedicated service executive (OS) or outsource the service provision to specialized providers, performance improves in terms of differentiation and customer satisfaction (Bustinza et al, 2015).…”
Section: -mentioning
confidence: 99%
“…We found that two main pillars support such product strategy, from one hand technical skills of the team and from the other the willingness to establish a good strategy to develop platforms that allow obtaining advantage from the existing knowledge in NPD teams (Figure 3A). The model also shows that these both dimensions are stronger when there is an effective interaction with external suppliers, bringing fresh knowledge from an external source (Ayala et al, 2017(Ayala et al, , 2018.…”
Section: Discussionmentioning
confidence: 87%
“…In order to take advantage from the knowledge generated during NPD, several scholars have studied the contribution of knowledge management strategies (e.g. Yam & Chan, 2015;Akroush & Awwad, 2018;Ayala et al, 2017Ayala et al, , 2018. When referring to NPD, one of the focus of knowledge management studies is the use of the generated knowledge to improve future or other concurrent projects.…”
Section: Introductionmentioning
confidence: 99%
“…Lamba and Singh (2019) propose a dynamic supplier selection model considering the carbon emissions in a big data environment. Ayala et al (2019) study the moderating role of service suppliers in product companies (servitization). With regard to the integration of service products, some scholars explored the resource selection and integration in third-party logistics service.…”
Section: Literature Reviewmentioning
confidence: 99%